Ectopic ACTH syndrome: clinicopathological correlations. Issue 6 (June 1978) - Singer, W; Kovacs, K; Ryan, N; Horvath, E
Abstract : Ten out of 164 cases of bronchogenic carcinoma showed pathological evidence at necropsy of the ectopic ACTH syndrome. All occurred in association with oat-cell carcinoma, constituting 19% of that group. The pathological features consisted of adrenocortical hyperplasia confined to the zona fasciculata and Crooke's hyaline change in the pituitary. Immunoperoxidase stainable ACTH was detected in the pituitary but not in the carcinoma tissue, a surprising finding, which may be due to the different nature of ACTH present in tumour tissue. The ectopic ACTH syndrome was diagnosed ante mortem in only four out of 10 patients on the basis of hypokalaemia and metabolic alkalosis. The lack of clinical pointers in all but terminal cases is discussed as well as possible measures for earlier diagnosis.